Pengaruh Penggunaan Teknologi Forensik Terhadap Akurasi Identifikasi Tersangka Dalam Proses Penyidikan - Annisa Nur Indar Parawangsa; Chintia Riduan Putri; Anisah Julianty Wahyuningbudi (Jurnal Kajian Hukum dan Pendidikan Kewarganegaraan, 2025)
The effectiveness of the use of forensic technology in improving the accuracy of suspect identification in criminal investigations. The main issue raised is the extent to which forensic technology, such as DNA analysis, digital fingerprinting, and biometric recordings, can improve the accuracy and speed of suspect identification by law enforcement officers. The research problem formulation in this study is how the use of forensic technology affects the accuracy of suspect identification in the investigation process. This study uses an empirical legal method with a qualitative approach, through literature review. Data are analyzed descriptively and analytically to assess the relationship between the application of forensic technology and the accuracy of investigation results. The results show that the use of forensic technology has a significant effect on improving the accuracy of suspect identification, reducing the potential for misdiagnosis, and accelerating the process of solving cases. In addition, the integration of forensic technology into the investigation system also increases the transparency and accountability of law enforcement officers. Thus, it can be concluded that the application of forensic technology plays a significant role in strengthening the fairness and effectiveness of the criminal justice system in Indonesia.